Hemorrhagic Cholecystitis after Warfarin Use for Deep Vein Thrombosis - Donn, Eric; Atkinson, Ian; McCague, Andrew (The Surgery Journal, 2018)
Hemorrhagic cholecystitis is an uncommon form of acute cholecystitis which can be rapidly fatal. It may be hard to detect as it frequently presents with symptoms found in other, more common diagnoses. We report the case of a 63 year old man recently started on anticoagulation for deep vein thrombosis who was found to have hemorrhagic cholecystitis.
Keywords: hemorrhagic cholecystitis; warfarin; anticoagulation; cholecystitis; deep vein thrombosis